Pola Interaksi Anak, Guru dan Orang Tua Selama Masa Pandemi Covid-19 Pendekatan Etika Komunikasi Islam - Abdullah Habib (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2021)
Abstract This article discusses the ethics of Islamic communication in the interaction of children, teachers and parents during the Covid-19 pandemic. The analysis results conclude that the communication pattern that can be categorized as a form of honest communication between parents, teachers, and students in the Al-Qur’an. The qawlan balîga pattern is translated into correct words, found in QS. An-Nis? '[4]: 62-63; The qawlan karîma pattern is translated with noble words, the qawlan maisûra pattern is translated with appropriate words; The qawlan ma?rûfa pattern is translated as a kind word; The qawlan layyina pattern is translated with gentle words, the qawlan sad?da pattern is translated with the right word; Keywords: Islamic communication ethics, interaction, children, teachers and parents.